KNITTING THE PAST, UNDERSTANDING THE PRESENT: A QUALITATIVE STUDY OF THE HISTORY, SOCIO-ECONOMICS, AND POLITICS OF WEST SALONGO VILLAGE (2011-2020) - Lahiya, Astrit Safitri; Manay, Helman; Malae, Andris K. (CV. Fahr Publishing, 2025)
Regional expansion is often considered a vital strategy to improve the effectiveness of local government and development. This study aims to explore the social, economic, and political dynamics of Salongo Barat Village during the period 2011-2020. The birth of this village was a response to the challenges of managing a large area, while being driven by community initiatives and support from the local government. Using a qualitative approach, data were collected through participatory observation, in-depth interviews with key informants, village heads, community leaders, and residents, and documentation studies from village archives and policies. The results of the study show that village expansion is not just an administrative reorganization, but an effective strategy to improve public services, accelerate infrastructure development, and optimize the potential of agriculture and plantations as the main pillars of the local economy. This period also highlights how the synergy between government policies and active community participation plays a crucial role in achieving economic stability and improving welfare in Salongo Barat Village. In conclusion, the expansion of Salongo Barat Village has successfully created a sustainable and adaptive social transformation, highlighting the importance of local autonomy in promoting community welfare.